ANALYSIS OF STRIDE SPACE-TIME VARIABLES: COMPARISON OF MALE AND FEMALE (Fiep Bulletin - online, 2014)
As walking is an easily accessible activity, it is practiced by many people as an alternative physical activity. Although two people do not walk in an identical manner, there are certain stride characteristics that are universal. These similar features may serve as a basis for the kinematic and dynamic description of muscle activity and others. The kinematic study of movement is fundamental for the biomechanical analysis of sports gestures and the physical activity. This study aimed to evaluate the space-time characteristics of the stride of walkers as a function of gender and speed and to compare the space-time characteristics of stride of male and female at different speeds. Twenty volunteers, 10 male and 10 female aged 23.2 (+ 4.76 years), beginner treadmill walkers, took part in this study. Each volunteer walked on the treadmill at 4, 5, and 6 km/h for 2 min in each phase. Data acquisition time was 30 seconds. The following stride space-time variables were selected for analysis: stride length (SP), double support time (DST), and single support time (SST), which were measured by kinemetry. It has been concluded that male and female present differences in stride (p < 0.05), being the SL, DST, and SST values at 4, 5, and 6 km/h larger for male. This difference may be caused by anthropometric factors. Furthermore, the increase in stride speed affects the behavior of the space-time variables of healthy individuals.
Keywords: Stride speed; kinemetry; space-time variables